BUDAYA KEMISKINAN MASYARAKAT KOTA (Studi Pada Keluarga Miskin Di Kelurahan Meranti Pandak Kota Pekanbaru) - Nanik Rachmawati (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2011)
This study aimstoexplain thesocial and economic characteristicsof poorinsubMerantiPandakonindividualandcommunitylevel, toknow thecharacter ofthe cultureof povertyof the poorinsub Meranti Pandakatthe individual and the community, andknowingthe pattern ofadaptationwhichis aculture of poverty, both at the level individual sand communities. Intheory, the cultureof povertyis apoorreaction to the irmarginal position withina class stratifiedsociety, highly individualistic, and characterized bycapitalism. Culturereflectsaneffort toovercomethe despairandhopelessnesswhich is amanifestationthatit is impossible to achieve successinlifein accordance with the values and objectives ofthe wider society. This research is categorized as descriptive research by conducting observations and interviews in depth to maintain the integrity of the object being studied. The unit of analysis and informants of this research are families living in Meranti Pandak village with a long stay in the top 10 (ten) years, and with different types of work and their relatively small incomes. The resultsof this studys howed that there was astrongef fortfromthemto survivein the current location ofresidence, althoug heve rynowinundated. Although the conditions that are less mennguntungkan the viewof many, but they feel happy and comfortable because every moment they canparticipate more or lessaccess to assistance that comes to the mas”victims of the flood. “ Reflection of the apathyshown by how they survive in the ircurrentresidence foral waystouched bytheassistance.